Anti-biofilm activity of chlorhexidine digluconate against Candida albicans vaginal isolates - Alvendal, Cathrin; Mohanty, Soumitra; Bohm-Starke, Nina; Brauner, Annelie (PLOS ONE, 2020)
Objectives Recurrent vulvovaginal candidiasis (RVVC) causes significant morbidity. Candida albicans is the main pathogen associated with both sporadic and recurrent candidiasis. Due to unsatisfactory treatment effect, the impact of chlorhexidine digluconate and fluconazole alone or in combination on C. albicans and biofilm was investigated. Methods Vaginal C. albicans isolates from 18 patients with recurrent candidiasis and commensals from 19 asymptomatic women were isolated by culture. Crystal violet, XTT and colony forming unit assay were used to analyze the effect of chlorhexidine digluconate and fluconazole on growth of C. albicans, formation of new and already established, mature, biofilm. Results Fluconazole reduced the growth of planktonic C. albicans. However, in established biofilm, fluconazole had no effect on the candida cells and was not able to disperse and reduce the biofilm. By contrast, chlorhexidine digluconate had a direct killing effect on C. albicans grown both planktonically and in biofilm. Chlorhexidine digluconate also dispersed mature biofilm and inhibited formation of new biofilm. No major differences were observed between commensal isolates and candida causing recurrent vulvovaginitis with respect to biofilm or growth after chlorhexidine digluconate treatment. Conclusion Biofilm is a problem in patients with recurrent vulvovaginal candidiasis reducing the effect of antifungal treatment. Development of new treatment strategies are urgently needed to decrease the recurrences. In already established biofilm, chlorhexidine digluconate dispersed the biofilm and was more effective in eradicating candida compared to fluconazole. Future treatment strategy may thus be a combination of chlorhexidine digluconate and fluconazole and prophylactic use of chlorhexidine digluconate to prevent biofilm formation and restrict infections.